Influence of Poles Embrace on In-wheel Switched Reluctance Motor Design - Yildirim, Merve; Kurum, Hasan (Ieee, 2018)
In this paper, influence of stator and rotor pole embraces on torque of In-Wheel Switched Reluctance Motor (IW-SRM) is investigated by numerical modeling based on Finite Element Method (FEM). There is very little work about the influence of the poles embrace on the motor design in the literature. This topic has not also been studied for IW-SRM yet. Therefore, this is a novel work and it is researched in this paper. Firstly, 3D numerical model of IW-SRM is built by using Ansys Maxwell Software Package. Then, IW-SRM is analyzed and output torque of the IW-SRM is calculated. The analysis of IW-SRM is realized for different rotor and stator pole embraces and the results of the output torque of IW-SRM taken for various rotor and stator pole embraces are compared with each other. As seen from the results, when the value of rotor pole embrace increases, the output torque of IW-SRM reduces. As a result in this study, the effects of different poles embrace are examined on the output torque of IW-SRM. Thus, proper pole embraces can be selected for optimum motor design.
18th IEEE International Power Electronics and Motion Control Conference (IEEE PEMC) -- AUG 26-30, 2018 -- World Trade Ctr, Budapest, HUNGARY
Keywords: in-wheel switched reluctance motor; torque; ansys maxwell; finite element method